2022
DOI: 10.1155/2022/4447484
|View full text |Cite|
|
Sign up to set email alerts
|

The Effectiveness and Safety of Ropivacaine and Medium-Dose Dexmedetomidine in Cesarean Section

Abstract: Objective: To study the effects of epidural anesthesia with different doses of dexmedetomidine and ropivacaine on postoperative hemodynamics and neonatal outcome of cesarean section parturients. Methods. A total of 90 parturients who underwent cesarean section admitted to our hospital from January 2019 to January 2020 were selected as the research objects and were divided into groups A, B, and C according to different dosages of dexmedetomidine, with 30 cases in each group. Groups A, B, and C were given dexmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Basic maternal information: Age, weight, height, gestational week, maternal VAS score and cervical canal dilatation; maternal sensory block (assessed using sterile cotton balls), motor block (assessed using Bromage score) [15] after 30 min of the analgesia protocol (where patients with a score of 0 can move all leg joints on their own, patients with a score of 1 can bend their knees and ankles, patients with a score of 2 can move only their ankles, and patients with a score of 3 have lost motor function in their leg joints); blood pressure (absolute value <90 mmHg defined as hypotension) and heart rate (<60 BPM defined as bradycardia), and fetal heart rate (<110 BPM defined as bradycardia), respiratory depression (oxygen saturation <90 %); maternal sedation [16] (awake with stress response defined as no sedation, awake but fatigued and sleepy defined as mild sedation, moderate sedation if awake, and severe sedation if not awake) and VAS scores; duration of the 1 st and 2 nd stage of labor; pH value of the umbilical artery of the newborn; Appearance, pulse, grimace, activity, and respiration (Apgar) score at 1 min and 5 min after birth; mode of delivery (vaginal vs. cesarean) and maternal nausea and vomiting, skin pruritus, and other adverse effects.…”
Section: Observed Indicatorsmentioning
confidence: 99%
“…Basic maternal information: Age, weight, height, gestational week, maternal VAS score and cervical canal dilatation; maternal sensory block (assessed using sterile cotton balls), motor block (assessed using Bromage score) [15] after 30 min of the analgesia protocol (where patients with a score of 0 can move all leg joints on their own, patients with a score of 1 can bend their knees and ankles, patients with a score of 2 can move only their ankles, and patients with a score of 3 have lost motor function in their leg joints); blood pressure (absolute value <90 mmHg defined as hypotension) and heart rate (<60 BPM defined as bradycardia), and fetal heart rate (<110 BPM defined as bradycardia), respiratory depression (oxygen saturation <90 %); maternal sedation [16] (awake with stress response defined as no sedation, awake but fatigued and sleepy defined as mild sedation, moderate sedation if awake, and severe sedation if not awake) and VAS scores; duration of the 1 st and 2 nd stage of labor; pH value of the umbilical artery of the newborn; Appearance, pulse, grimace, activity, and respiration (Apgar) score at 1 min and 5 min after birth; mode of delivery (vaginal vs. cesarean) and maternal nausea and vomiting, skin pruritus, and other adverse effects.…”
Section: Observed Indicatorsmentioning
confidence: 99%
“…Shivering is observed in over 57% of pregnant women undergoing cesarean section, and its occurrence follows a seasonal pattern in which it is observed predominantly in autumn and winter [1,2]. Studies have shown that shivering in pregnant women after a cesarean section may lead to increased intraocular and intracranial pressure, subjective feeling of severe discomfort, reduced quality of life, and increased carbon dioxide production due to anaerobic respiration [3].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%